Etnomanejo de açaizal nativo como ferramenta de organização da comercialização de produção do açai, na comunidade extrativista Bom Jesus, Resex Mapuá, Breves, Pará - SILVA, Vanilce Gomes da (2022)
The present work, carried out in the Bom Jesus community of the Marajó archipelago of Pará, has the perspective of devising a community action plan that establishes strategies aimed at extracting açaí, based on the idea of ethnodevelopment. The various aspects that encompass the challenges that characterize the reality of riparian peoples are evident and provide enough "raw material", in addition to measuring how large the demand is, as well as the need to deal with a subject that is still little evidenced in the literature, of those who are inserted in the environment and who live daily the hardships of not having effective policies that provide the inhabitants with conditions to produce and sell what is harvested. Within this issue, numerous prerogatives are included, which will be highlighted throughout this work, as well as possible solutions that will contribute to a sustainable development with quality through management practices of açai groves.